Peran Masyarakat dalam Mengembangkan Ekowisata Candi Tegawangi - Sya’diyah, Lailatul (Lembaga Kajian, Penelitian dan Pengembangan Mahasiswa Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
The purpose of this study is to track down, to dig and to preserve historical relic of Tegawangi temple as a tourism asset advocating society’s local economy in Kediri. This research is qualitative descriptive, by using descriptive analysis approach done by collecting data from the activities and livelihood of local society. Public participation in developing a historical relic in their area as an object of tourism becomes a major measure in the success of an object itself in this global competition in the world. Thus, community based tourism is a method which was initiated to develop local citizens and empower people’s economy by utilizing local attraction of Tegawangi temple. Not only to develop the economy but also to engage community in preserving cultural heritage. Historical relic such Tegawangi temple are hoped to be able to boost the spirit of nationalism, meant more love domestic product. Bangsa Indonesia. Sejatinya pendidikan pesantren yang tetap mempertahankan kurikulum mandirinya tetap menjadi pilihan, tanpa tergeser sedikitpun meskipun dunia semakin modern dan memasuki era globalisasi. Pendidikan pesantren sebagai pendidikan yang berbasis nilai (value oriented) menjadi satu-satunya pendidikan alternatif yang mampu membentuk jati diri manusia. Pendidikan karakter masuk menjadi fokus utama dalam membentuk manusia seutuhnya. Melalui pesantren inilah dirasa mampu mewujudkan manusia seutuhnya dengan peng-internalisasian nilai yang dengan sengaja ditanamkan.